Essays in finance - Mohd Rasid, Mohamed Eskandar Shah (2012)
This thesis which compromise of three essays focuses on the theme of valuation, value premium anomaly, financing behaviour and emerging markets. The first essay studies the value growth puzzle in the context of conflict of interest between taxable and institutional investors. We model this conflict in a rational expectations framework and demonstrate how the differences in firm's characteristics (in terms of value versus growth) and the risk profile of the investors can explain the shape of CAPM's frontier in the overall economy without involving the beta parameter. We also explicate that the changes in taxable and non-taxable investors profile in a dynamic environment rationalize the value growth premium as illustrated by Malkiel (2003). Finally, our approach shed light on the issues raised by Shiller (1979,1981) and LeRoy and Porter (1981) that stock [bond] prices are too volatile to be rationalized by the discounted value of their expected dividends [coupon payments].